Alterations of Hippocampal Place Cells in Foraging Rats Facing a "Predatory'' Threat - Kim, Eun Joo; Park, Mijeong; Kong, Mi-Seon; Park, Sang Geon; Cho, Jeiwon; Kim, Jeansok J. (CELL PRESS, 2015)
Fear is an adaptive mechanism evolved to influence the primal decisions of foragers in "approach resource-avoid predator'' conflicts [1-3]. To survive and reproduce, animals must attain the basic needs (food, water, shelter, and mate) while avoiding the ultimate cost of predation [4]. Consistent with this view, ecological studies have found that predatory threats cause animals to limit foraging to fewer places in their habitat and/or to restricted times [5-7]. However, the neurophysiological basis through which animals alter their foraging boundaries when confronted with danger remains largely unknown. Here, we investigated place cells in the hippocampus, implicated in processing spatial information and memory [8-10], in male Long-Evans rats foraging for food under risky situations that would be common in nature. Specifically, place cells from dorsal cornu ammonis field 1 (CA1) were recorded while rats searched for food in a semi-naturalistic apparatus (consisting of a nest and a relatively large open area) before, during, and after encountering a "predatory'' robot situated remotely from the nest [11]. The looming robot induced remapping of place fields and increased the theta rhythm as the animals advanced toward the vicinity of threat, but not when they were around the safety of the nest. These neurophysiological effects on the hippocampus were prevented by lesioning of the amygdala. Based on these findings, we suggest that the amygdalar signaling of fear influences the stability of hippocampal place cells as a function of threat distance in rats foraging for food.
Keywords: OBJECT RECOGNITION; CORTEX LESIONS; AMYGDALA; FEAR; STRESS; MEMORY; ENVIRONMENT; PLASTICITY; AVOIDANCE; MODEL